2007
DOI: 10.1111/j.1540-8183.2007.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity in Clinical Outcomes Following Primary Percutaneous Coronary Intervention for ST Elevation Myocardial Infarction: Influence of Process of Care

Abstract: Previous studies have shown that compared with white patients, non-white patients with ST elevation myocardial infarction (STEMI) have worse clinical outcomes. Differences in co-morbidities, extent and severity of coronary artery disease, health insurance, and socioeconomic status have been identified as possible reasons for this disparity. However, an alternative explanation for such observed disparities in outcomes could be differences in process of care. For example, in most of these studies, non-white pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…Thus, some of the pertinent data were not available and precluded certain analyses such as evaluation of risk assessment tools with CRP. Generalizability of the performance of the risk scores in this cohort to other populations may be limited as clinical manifestation of sarcoidosis and baseline risk of CVD vary among ethnic groups 2730 and the population of Olmsted County is predominately of Northern European ancestry. It is possible that the calculators may perform even worse among Blacks with sarcoidosis as they tend to have a more severe disease and, thus, more inflammatory burden and exposure to glucocorticoid.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some of the pertinent data were not available and precluded certain analyses such as evaluation of risk assessment tools with CRP. Generalizability of the performance of the risk scores in this cohort to other populations may be limited as clinical manifestation of sarcoidosis and baseline risk of CVD vary among ethnic groups 2730 and the population of Olmsted County is predominately of Northern European ancestry. It is possible that the calculators may perform even worse among Blacks with sarcoidosis as they tend to have a more severe disease and, thus, more inflammatory burden and exposure to glucocorticoid.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that if all patients with STEMI were treated with an identical protocol for primary PCI, there would be no racial disparity in clinical outcomes. 32 Hence, although it is convenient to label patients by race, factors that relate to SES such as income, education, housing, and social awareness are probably more important in health‐related outcomes. Socioeconomic position has been speculated to be a greater impediment to optimal cardiovascular health rather than “biologically implausible surrogates of race and sex.” 33 …”
Section: Discussionmentioning
confidence: 99%
“…(26) In addition, non-whites are less likely to receive reperfusion therapy or be transferred for PCI. (27)(28)(29) Many explanations have been suggested as to the cause of this disparity including worse CAD, abundant co-morbidities, worse socioeconomic status, and geographic location with impaired access to specialists.…”
Section: Discussionmentioning
confidence: 99%
“…(27,30) However, it is difficult to ascertain the predominant factors associated this disparity especially with a protocol that should treat all-comers equally. With the data available it is unclear if some of these patients that did not undergo PCI went on to get bypass grafting due to more advanced CAD or not.…”
Section: -14 -mentioning
confidence: 99%
See 1 more Smart Citation